Kajian Terhadap Permainan Game online Dalam Implementasi Pemenuhan Hak Anak - Yuni Ledi Syntiani; Fricean Tutuarima; Titus Gaite (Jayapangus Press, 2022)
Playing is part of children's rights that must be fulfilled by parents to children, as stated in Article 11 of Law no. 23 of 2002 concerning Child Protection. Currently in the children's play environment many game that can be accessed by utilizing the internet network are called online game. As for the reality on the ground, not all parents give their children the opportunity to play online game. This study aims to determine the study of online game play in the implementation of the fulfillment of children's rights in Rijali Village, Sirimau District, Ambon City. The method used in this study is a qualitative method to describe the data in written form. The results show that the existence of online game has an impact on children's health and learning activities which are decreasing. Responding to the existence of online game, some parents make efforts to prevent excessive playing habits. Efforts are given to parents in the form of advice, time limits, and more control over children. As for the handling efforts, there are several obstacles faced by parents. In general, parents understand that children cannot limit playing online game because parents realize that learning is part of children's rights that must be fulfilled.